Dampak Ekonomi Penggalian Pasir Kabupaten Manokwari (Studi Kasus Penggalian Pasir Pantai Amban Kelurahan Amban) - Agtisrum Agtisrum; Elina Relawaty Situmorang; Danny Waimbo (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2021)
Sand excavation in Amban Pantai Village began to be managed routinely and commercially in 1995, so this study aims to analyze qualitatively the economic impact of the sand mining business. The results of the study indicate that the economic impact of the sand quarrying business for ulayat owners is to become the main source of livelihood and investment in human resources in the field of education for their children. The economic impact for sand mining entrepreneurs is the profit from selling services and absorbing labor. The economic impact for company workers is additional income from the company, while local workers are job opportunities and form a dream to become an entrepreneur. The economic impact for the kiosk business around the excavated area is the additional turnover of goods sold, especially mineral water, while the economic impact for the food stall business is the turnover of the food sold. Galian Pasir di Kelurahan Amban Pantai mulai dikelola secara rutin dan komersil Tahun 1995, maka penelitian ini bertujuan untuk menganalisis secara kualitatif dampak ekonomi usaha galian pasir tersebut. Hasil penelitian menunjukkan bahwa dampak ekonomi usaha galian pasir bagi pemilik ulayat yaitu menjadi sumber matapencaharian utama dan investasi sumberdaya manusia bidang pendidikan bagi anak-anaknya. Dampak ekonomi bagi pengusaha galian pasir adalah keuntungan penjualan jasa dan menyerap tenaga kerja. Dampak ekonomi bagi buruh perusahaan yaitu penghasilan tambahan dari perusahaan, sementara buruh lokal yaitu lapangan pekerjaan dan membentuk mimpi menjadi pengusaha. Dampak ekonomi bagi usaha kios sekitar daerah galian adalah tambahan omzet barang yang terjual terutama air mineral, sementara itu dampak ekonomi bagi usaha warung makan adalah omzet makanan yang terjual.